Tracking Oral Nanoparticle Uptake in Mouse Gastrointestinal Tract by Fluorescent Labeling and t-SNE Flow Cytometry - Rabeya Mow; Michal Kuczma; Xiaodi Shi; Didier Merlin; Chunhua Yang (Bio-Protocol)
The growing demand for advanced analytical techniques to explore complex cellular targets of nanotherapeutics has driven the development of innovative methodologies. This protocol presents a refined approach for fluorescent labeling and flow cytometric analysis of colonic cells following oral lipid nanoparticle (LNP) treatment, focusing on LNP uptake in colonic cell subpopulations in a DSS-induced colitis mouse model. By integrating optimized fluorochrome selection and gating strategies with advanced t-distributed stochastic neighbor embedding (t-SNE) analysis, this method enables precise identification and multidimensional visualization of LNP-targeted epithelial and macrophage populations under the complex conditions of inflamed colon tissue. Building on our previous studies demonstrating the effectiveness of nanoparticles in targeted drug delivery, this approach highlights the utility of flow cytometry for assessing uptake efficiency and cellular targeting. Unlike conventional protocols, it incorporates t-SNE for enhanced multidimensional analysis, allowing for the detection of subtle cellular patterns and the delineation of intricate clusters. By addressing gaps in traditional methodologies, this protocol provides a robust and reproducible framework for investigating in vivo cellular targets and optimizing drug delivery strategies for nanomedicines.